2023
DOI: 10.3390/v15122403
|View full text |Cite
|
Sign up to set email alerts
|

High Seroprevalence of Severe Fever with Thrombocytopenia Syndrome Virus Infection among the Dog Population in Thailand

Keita Ishijima,
Thanmaporn Phichitraslip,
Nattakarn Naimon
et al.

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne zoonotic disease caused by the SFTS virus (SFTSV). In Thailand, three human cases of SFTS were reported in 2019 and 2020, but there was no report of SFTSV infection in animals. Our study revealed that at least 16.6% of dogs in Thailand were seropositive for SFTSV infection, and the SFTSV-positive dogs were found in several districts in Thailand. Additionally, more than 70% of the serum samples collected at one shelter possessed virus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In Thailand, the presence of stray or neglected companion dogs, and the widespread popularity of dog ownership, pose an important source of infection 46 , as clinical signs of SFTSV-infected dogs are relatively mild, making the diagnosis difficult and barely attracting enough attention to their owners and veterinary professionals 37 . Moreover, a SFTSV seroprevalence study published in 2023 and conducted in dogs, demonstrated a total seroprevalence of 16.6% (ELISA and seroneutralization) in the provinces of Bangkok, Chachoengsao, Samut Prakan, Rayong, and Chonburi, suggesting that infection among the canine population may be similar to those in endemic regions of China 4 .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In Thailand, the presence of stray or neglected companion dogs, and the widespread popularity of dog ownership, pose an important source of infection 46 , as clinical signs of SFTSV-infected dogs are relatively mild, making the diagnosis difficult and barely attracting enough attention to their owners and veterinary professionals 37 . Moreover, a SFTSV seroprevalence study published in 2023 and conducted in dogs, demonstrated a total seroprevalence of 16.6% (ELISA and seroneutralization) in the provinces of Bangkok, Chachoengsao, Samut Prakan, Rayong, and Chonburi, suggesting that infection among the canine population may be similar to those in endemic regions of China 4 .…”
Section: Resultsmentioning
confidence: 97%
“…Since it requires different hosts for each blood meal, and in the era of globalization and climate changes, it has been suggested that ticks exposed to high temperatures attached more to humans, potentially increasing the risk of transmission of certain zoonotic pathogens 11 . Therefore, we collected 433 Rhipicephalus sanguineus sensu lato ticks from dogs in rural communities of Chachoengsao Province, Thailand, where one human case of SFTSV was identified in 2020 14 , and a seroprevalence of 11.1% was found in dogs in 2022 (confirmed by FRNT50) 4 . Two hundred fifty-three (58.4%) ticks were male, 55 (12.7%) were females and 125 (28.9%) engorged female ticks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations